Pott’s Disease in Pregnancy: A Case Report and Review - Yusuf, N; Ali, A; Ahmad, Q; Rahman, L; Nigar, T (TAJ: Journal of Teachers Association, 2009)
Spinal tuberculosis (Pott's disease) during pregnancy reported to be rare & can be associated with destruction of the intervertebral disc & adjacent vertebrae that can lead to cord compression & thereby paraplegia or quadriplegia. Delay in diagnosis is common & most cases are diagnosed when paraplegia has already been occurred. This serious complication requires special attention during pregnancy & delivery. Here we reported a case of term pregnancy with Pott's paraplegia. As the patient had complete motor & sensory loss from D7 level, (above the level of umbilicus to the lower limbs) LUCS was done without anesthesia & a healthy female baby was delivered. She did not require any analgesia post operatively. TAJ 2009; 22(1): 282-286